Issues and Prospects in Continuing Education for Skills Development of Automobile Technicians in Nigeria - Fajimi, Babatunde Ayoola; Kester, Kehinde Oluwaseun; Ukpabi, Donatus (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
The automobile technicians are catalytic to the industrial revolution, employment generation, human capital development, and economic growth in the automotive industry in Nigeria. There is, however, a lack of competencies among them that has generated concerns in the community of practice. The study explored challenges of skills development among automobile technicians and examined the prospects of continuing education to enhance their skills development in the automotive industry. The study adopted a qualitative research method and reviewed journals, books, news reports, and official publications to discuss the key concepts of continuing education, skills development, and mainstreaming of automobile technicians in the informal sector to the national policy framework to transform the automotive industry for human capital development and economic growth in Nigeria. The absence of continuing education in the occupational practices of automobile technicians has created skills development crises in the automotive industry and is evidenced by a shortage of skilled labour, aging demographics, the prevalence of quackery, lack of requisite work knowledge, non-availability of sustainable continuing education programmes, lack of opportunities for continuing professional development, sectoral policy disconnect with human capital development practice in the industry, and funding. The implementation of continuing education programmes for the skills development of automobile technicians can create opportunities to enhance improved competencies, transform human capital development, and engender value creation and exceptional service delivery in the automotive industry through the transformative work environment and delivery of collaborative skills development programmes. The government should mainstream and implement grassroots policies for inclusive collaboratives to certify automobile technicians through continuing educational development programmes in the automotive industry.